1974
DOI: 10.1083/jcb.61.3.723
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy and Electron Probe Analysis of Mitochondrial Cation Accumulation in Smooth Muscle

Abstract: The contractile responses to barium and the ultrastructure and ionic composition of mitochondria were studied in vascular smooth muscle . In normal rabbit portal anterior mesenteric vein (PAMV) and main pulmonary artery (MPA) smooth muscle mitochondria were frequently associated with the surface vesicles . The Electron probe X-ray microanalysis also showed a highly significant (P < 0 .001) correlation of P with mitochondrial Ba, in an estimated elemental ratio of approximately 3 Ba/4 P . Mitochondrial granules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

1975
1975
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(57 citation statements)
references
References 57 publications
4
52
1
Order By: Relevance
“…Intracellular organelles such as sar coplasmic reticulum and mitocondria, cyto plasm and plasma membrane have been usually accepted as Ca locations in smooth muscle cells (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular organelles such as sar coplasmic reticulum and mitocondria, cyto plasm and plasma membrane have been usually accepted as Ca locations in smooth muscle cells (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The hearts were perfused through the aorta with 2% glutaraldehyde and kept in 2% glutaraldehyde overnight at 4°C. Small pieces (ϳ1-mm in diameter) of the lower left ventricle were then postfixed, stained, and embedded following the standard procedure (18,19): 2% osmium tetroxide for 2 h, saturated aqueous uranyl acetate for 1.5 h, dehydrated in a series of graded alcohols, and embedded in Spurr's resin. Sections were poststained by lead citrate and imaged in a Philips CM12 electron microscope at 120 KeV equipped with a SIA 8C 2,000 ϫ 3,000 CCD camera (Duluth, GA).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, we performed some experiments using titanium dioxide nanoparticles (crystallite anatase size is in the sub-10 nm range) to investigate whether the mitochondrial exposure to particles induced the same response, but we found that titanium dioxide nanoparticles did not induce the same alterations in mitochondrial function even if the RCI decreases in the same magnitude. First, we observed alterations in mitochondria after PM 10 exposure, including unpacked and disrupted cristae with a decrease in parallel alignment and decrease in mitochondrial dense granules, which has been reported as calcium granules observed by TEM (Somlyo et al 1974). Structural abnormalities are strongly associated with metabolic changes, as reported here, for example, disruption in membrane integrity affected RCI in isolated mitochondrial from endotoxin-induced liver damage (Crouser et al 2002).…”
Section: Discussionmentioning
confidence: 57%